2009
DOI: 10.1002/ijc.24400
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog and epithelial‐mesenchymal transition signaling in normal and malignant epithelial cells of the esophagus

Abstract: It has been established that the Hedgehog (Hh) and epithelialmesenchymal transition (EMT) signals act on morphogenesis of embryonic and adult tissues. Recently, both signals have been involved in tumor malignancy. However, little is known as to whether Hh and EMT signals act on normal and malignant epithelial cells in the esophagus. By laser microdissection (LMD)-based microarray and reverse transcription polymerase chain reaction in the undifferentiated and differentiated epithelial cells of the esophagus, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 32 publications
3
65
1
Order By: Relevance
“…SHH is active only in stem cells and/or endodermal progenitor in adults (16,23). Recent studies showed that aberrant signaling of this pathway is involved in a variety of human cancers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The HH pathway essentially consists of PTCH, the motive protein, SMOH, and the transcriptional factors GLI2 and GLI3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SHH is active only in stem cells and/or endodermal progenitor in adults (16,23). Recent studies showed that aberrant signaling of this pathway is involved in a variety of human cancers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The HH pathway essentially consists of PTCH, the motive protein, SMOH, and the transcriptional factors GLI2 and GLI3.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as a transcription factor, GLI1 expression is a good indicator of HH pathway activation. Recent studies showed that Gli1 controls several biological characteristics, such as proliferation and invasion, in several types of cancers (17,19,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zfhx1b gene (44.810557 Mb), which encodes zinc finger homeobox 1b protein, showed the highest expression heritability correlation in the liver (r 5 -0.919, P < 4.99 -39 ), but none in brain. The Zfhxb1 protein is a Smad-interacting transcriptional corepressor involved in Wnt and hedgehog signaling (Bassez et al, 2004;Verstappen et al, 2008;Isohata et al, 2009). Detrimental variants of the gene cause the developmental disorder Mowat-Wilson syndrome, which presents with multiple congenital deficits, including mental retardation (Zweier et al, 2002).…”
Section: Identification Of Candidate Chromosome 2 and 7 Modifier Genesmentioning
confidence: 99%
“…[5][6][7][8] Generally, the loss of E-cadherin is considered a common indicator for the onset of epithelial-mesenchymal transition, and it has been shown that Snail-dependent E-cadherin repression is one of the most important mechanisms for E-cadherin loss in esophageal squamous cell carcinoma. 5,8 However, there are some limitations in these studies due to the small number of cases investigated, and very little is known about the clinical significance of detailed epithelial-mesenchymal transition sub-phenotypes in esophageal squamous cell carcinoma.…”
mentioning
confidence: 99%